Experiencing temporal patterns of action learning and the implications for leadership development. Issue 1 (March 2021) - McCray, Janet; Warwick, Rob; Palmer, Adam; Thompson, Thomas
Abstract: The purpose of this paper is to analyse the ongoing effects of a United Kingdom situated Doctor Leadership Development Programme (LDP) which used action learning (AL) as the vehicle of practice. The aims of the research are firstly to gain insights into the meanings given to the LDP experience two years on by a cohort of doctors with senior leadership roles. Secondly, to establish what the development tool applied, that of Action learning (AL), offered these senior doctors and their practice as they attempted to facilitate change. An interpretive design is applied and the research is context specific, capturing a local experience of leadership over time. Participants were invited to take part in semi-structured interviews which were used as the data collection method. Study findings show that at a critical point for the organisation, the AL model of facilitation built a bridge between individual and collaborative action which has been sustained over time. In doing so new social support processes were created which enhanced the individual doctor's leadership style to move towards that of a collective leadership model. Paper Highlights: Reports ongoing effects of Action Learning experience two years on. Action Learning continues to impact on the networking practice of doctors. Action Learning enabled doctors to become more collaborative leaders. Long-term effects of Action L earning reported can assist workforce planners.